Asava Arista: an Medicated Alcohol Critical Review - Prajwal, Gurav; Mahadev, Badiger; Shreekant , Patil; Satish , Vasan (International Research Journal of Ayurveda & Yoga, 2022)
Ayurveda since ancient time’s renowned system of medicine in India. But it has got such an efficacy to cure the wide ranges of diseases. Asava arishta has evolved over time to include a variety of formulations that are prescribed for a variety of diseases. The pharmacological processing of asava and arishta reported in ayurvedic literature is rigorously examined in this paper. Inspection of the constituents required for preparation, including their composition, dravadravya (liquid), sandhaneeya dravya (fermenting materials), prakshepaka dravya (additives), madhura dravya (sweetening agents), sandhana paatra (fermentation vessels) used, samskaras prior to sandhana, method of preparation, sandhana Asava and arista are considered as exclusive formulation as per shelf life is concerned. These preparations are mainly used in case of Agni mandyata. These use of asava arista have led craze among the consumers due to its quicker absorption, long shelf life.